Olympia and the Olympieia: the origin and the dissemination of Olympian Zeus´ cult in Greece in the sixth and fifth centuries B.C. - Laky, Lilian de Angelo (Revista Archai, 2010)
The goal of this article is to present the dissertation research which studies the Olympian Zeus’ temples (Olympieion) built during the sixth and fifth centuries B.C. The intention is to understand how Olympia was responsible for the origin and dissemination of Olympian Zeus´cult through the Greek world. From the poleis survey that consecrated these temples to the deity and by the mapping of the cult in association to textual informations we will discuss the Olympios epiteth and the name Olympieion, the spacial configuration of the Olympian Zeus sanctuaries and the relationship of the cult and the tyranny.